PENGARUH PEMBERIAN REWARD TERHADAP DISIPLIN BELAJAR SISWA KELAS V DI SDN 006 TERPADU KUBANG JAYA KABUPATEN KAMPAR - Annisa Aulia Putri; Siti Quratul Ain (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Student learning discipline at V SDN 006 Terpadu Kubang Jaya is still relatively low. The aim of this research is to find out whether or not there is an effect of giving rewards on the learning discipline of class V students at SDN 006 Terpadu Kubang Jaya, Kampar Regency. The research method is quantitative with a population of 32 class V students with a sampling technique using purposive sampling. So the sample is 32 students. Data was collected through a questionnaire and processed using hypothesis testing with the help of SPSS Version 22. The results of the research showed that the value of itcount i>ittable (3.313> 2.042), meaning that iHa was accepted and iHo was rejected. Based on this, it can be concluded that the positive and significant influence of rewards on the learning discipline of class V students at SDN 006 Terpadu Kubang Jaya, Kampar Regency is 26.8% on student learning discipline (Y).